A randomized, single-blinded cross-over trial of ischemic preconditioning in Raynaud's phenomenon. Issue 3 (September 2017) - Neferu, Ramona; Vanderhoek, Louise; Hewitt, Sara; Nevskaya, Tatiana; Pope, Janet E.
Introduction: Ischemic preconditioning (IPC) is protective against future ischemia, with brief cycles of ischemia and reperfusion leading to the release of circulating endogenous compounds from ischemic cells. IPC may increase vasodilatory substances and improve Raynaud's phenomenon (RP). We hypothesized that IPC would be more effective than sham in RP treatment. Sample size required 18 participants to detect 5 fewer RP attacks per week. Methods: This was a randomized single-blinded cross-over trial. The IPC intervention of inflating a standard blood pressure cuff on the upper arm (200 mmHg) and sham intervention (60 mmHg) were performed 3 times per week for 2 weeks, with a 2-week washout period between IPC and sham interventions. Cuff inflation was performed 4 times for 2.5 minutes, with 2.5 minutes between cuff inflation. Participants completed a daily diary on RP disease activity. Results: Eighteen participants were enrolled (17 with secondary RP and 1 with primary RP); mean age 60.8 (SD 9.4) years, 89% female; and mean number of RP attacks/2 weeks in screen was 16.9 (SD 11.3). With IPC versus sham, results were not significant including an increase of 0.5 RP episodes/week (SD: 10.0; p = 0.84), decrease of 55.6 minutes per week (SD 516.4; p = 0.66), and a decrease in average severity of 0.4 points (on a scale of 0 to 10) (SD 12.9; p = 0.88). Secondary outcomes were also not significant. Conclusions: No significant differences in RP disease activity were found between IPC and sham. This could be due to lack of effect of IPC on RP, too few treatments, or sham having a partial effect.